Утилізація та напрями використання метану на шахтах України - Perov M.O.; Makarov V.M.; Novytskyi I.Yu. (General Energy Institute of the National Academy of Sciences of Ukraine, 2019)
The article examines and analyzes the state and problems of extraction and subsequent utilization of methane from the coal deposits of Ukraine, including the Donbass mines controlled by the Ukrainian authorities. Coal deposits of almost all mines in Ukraine are methane-bearing. Methane is continuously released into the mine space naturally, many mines are dangerous due to the sudden ejection of large volumes of methane, and the development of a coal seam intensifies the methane release.Methane with mine air in certain concentrations forms a fire-hazardous or explosive mixture, having neither color nor smell, and its presence can be detected only by special devices. There are no few cases of explosions and fires in mines, leading to the death of miners. Not being a toxic gas per se, methane nevertheless “dilutes” mine air, reducing the oxygen concentration in it, which negatively affects the working conditions of underground mine personnel.Taking this into account, we see that the degassing of mines is an urgent problem for the coal mining industry. Degassing can be carried out previously by drilling wells in coal seams (from the surface or shaft of the mine) and airing (ventilation). However, methane emissions from degassing systems directly into the Earth’s atmosphere are harmful for the environment, since methane is a greenhouse gas whose activity is by 21–25 times higher than that of a common greenhouse gas such as carbon dioxide.Therefore, the second urgent problem is the utilization of extracted methane. In addition, methane is a valuable high-calorific energy resource, more environmentally pure than coal and oil products.The article analyzes the potential reserves and distribution of methane volumes in coal masses, considers the degree of methane degassing and utilization in Ukraine, gives the forecasted volumes of methane emissions from mines in the territory controlled by the Ukrainian authorities. The possible acceptability of various methane-use methods was determined depending on factors such as methane flow rate, concentration, consumer distance, etc.As a conclusion, we see that, under conditions of the deficit of own natural gas reserves in the bowels of Ukraine and the state's dependence on imported fuel supplies, coal methane should take its rightful place in the formation of the national fuel-and-energy balance.